Nurses' knowledge, attitude, practice and barriers towards the use of evidence based nursing practice (EBNP) at government Hospital in Malaysia - a/p Subramaniam, Sivasangari (2015)
In the nursing profession, EBNP makes a positive contribution to healthcare outcomes, care delivery, clinical teaching and research. The research objective was to determine the nurses’ knowledge, attitude, practice of EBNP and barriers to adopt EBNP in four hospitals in Malaysia, Hospital Universiti Sains Malaysia (Hospital USM), Hospital Pulau Pinang (HPP), Hospital Sultan Abdul Halim (HSAH) and Hospital Seberang Jaya (HSJ). A cross-sectional study was conducted from January until December 2012 among nurses working in all disciplines, on shift or day time duties in four selected hospitals. The questionnaire was adapted from a Singapore study. The data were analysed with SPSS version 21.0, using descriptive statistics, Independent T-Test, One- Way ANOVA and Multi-Factorial ANOVA. Results showed that among the nurses working in four different Malaysian hospitals, nearly 50% knew what the evidence based practice meant. The items assessing the attitude showed a large number nurses responding that they did neither agree nor disagree with statements provided. The majority of the remaining nurses tended to show a rather positive attitude except when asked about how the workload interfered with their EBP practice. Most nurses recognized there were many barriers to EBP in their working place. The significant mean differences of practice on EBNP between senior and junior nurses were observed for the statements 1, 2, and 3 (p=<0.001), (p=0.005) and (p=0.028) respectively. Multifactorial ANOVA analysis used to determine the effect of academic qualification, working place, working experience and training on nurses’ knowledge towards EBNP. In conclusion, this study may have helped to increase understanding of knowledge, attitudes, practice and barriers to adopt EBNP to the utilization of research by nurses through an exploration of perceived barriers and facilitators on the part of nurses.